Orchiectomy In A Wild Boars - Kumar, Vijay; Raj , Anshu (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Surgical castration in animals without anaesthesia has been in practice throughout the world . But now a days many countries have banned on surgical castration without anaesthesia. The wild Boars belongs to the schedule - III animals under IUCN list of wild life conservation act of 1972. The hunting of the wild boars for meat purpose is prohibited under wild life protection act. So the population of wild boars can be controlled only by the methods of sterilization where there is large population explosion of the wild boars. The castration of the wild boars in the present case has been done in captivity in order to keep the number of the wild boars as per central zoo authority guidelines.